Navigating equity in global access to genome therapy expanding access to potentially transformative therapies and benefiting those in need requires global policy changes - Lee, Tsung-Ling; Sawai, Tsutomu (Frontiers in Genetics, 2024)
In December 2023, the US Food and Drug Administration and the UK Medicines and Healthcare Products Regulatory Agency granted the first regulatory approval for genome therapy for sickle cell disease. This approval brings hope to those suffering from this debilitating genetic disease. However, several barriers may hinder global patient access, including high treatment costs, obtaining informed consent for minors, inadequate public health infrastructure, and insufficient regulatory oversight. These barriers reflect the structural inequalities inherent in global health governance, where patient access often depends on social and institutional arrangements. This article addresses concerns around informed consent, treatment costs, and patient access, and proposes corresponding policy reforms. We argue that these discussions should be framed within a broader global context that considers social and institutional structures, global research priorities, and a commitment to health equity.